Advances in utilization of wastewater in agricultural practice: a technical note - Odoemena, Kenneth Ikenna; Kamal, Md. Rowshon; Che Man, Hasfalina (John Wiley and Sons, 2020)
This paper has endeavoured to produce a technical note on the hazards that humans and the environment face with the burden of wastewater irrigation on crops and the soil. Reports based on past and present issues related to wastewater used in irrigation of crops and the health implications when it is applied in the arable field for irrigating crops have been considered broadly. It is conclusive that wastewater has polluted and contaminated crops and soil when not properly treated before being applied for irrigation purposes. The crop effects and advantages of wastewater reuse in agriculture are of extensive application because of a lack of water in numerous parts of the world. Besides, the impacts of wastewater systems should be assessed not only from the perspective of social, monetary and natural viewpoints, but in addition from the sustainable improvement point of view; thus this paper surveyed the sustainability, benefits, impediments, developments and innovations of using the wastewater in water systems for agriculture. Wastewater treatment must be further advanced to address developing concerns such as amount and quality. More effective decentralized wastewater administration frameworks must be set up to provide the approach to abridge the cost of wastewater treatment. Finally, we require suitable strategies to catch and convey water, secure soil, reuse wastewater and streamline its administration.